(untitled) (Update Dental College Journal, 2016)
With the advent of new innovative system Componeer, the conventional porcelain veneer and composite restoration in the field of aesthetic dentistry has become minimal now. The Componeer system grants superior aesthetics along with ease of handling, no or minimal preparation, single appointment, no psychological trauma to patient and last but not least is economical. This article describes management of stained teeth by recently introduced novel system Componeer on which there is paucity of literature. Update Dent. Coll. j: 2016; 6 (1): 40-42